(untitled) (Journal of Enam Medical College, 2012)
In the urinary tract, foreign body is most commonly found in the urinary bladder. It is commonly self-inflicted but can rarely be introduced by other person. Various types of foreign bodies have been reported, which includes infusion set, aluminum rod, gold chain, pearl, fish, pencil etc. Here we report a case of a 28-year young man who gave the history of forceful introduction of a long wire of mobile charger into the bladder by another person. It could not be removed by himself and by the local doctors. Then he was referred to Enam Medical College & Hospital and subsequently was removed by suprapubic cystostomy. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11139 J Enam Med Col 2011; 1(1): 41-42